Digital Writing Technologies in Higher Education: Theory, Research, and Practice - (:unkn) unknown (Springer, 2023)
Digital writing, in simple terms, is writing using a digital environment or tool. As with literacy more broadly, for many of us digital environments and tools are increas- ingly prevalent in our writing endeavors. And yet in the field of digital writing, we have no comprehensive overview of which technologies are used in writing, how, when, and where they are used, and what their impact is on writers and their writing processes. This book aims to fill that gap. This introduction sets the stage for the book starting from the inception of digital writing and proceeding through three phases of transformation leading up to the present. We point out the challenges for research and practice in the field of digital writing targeted in this book. We preview how each chapter contributes to a systematic account of digital writing technologies, which builds on past scholarship and sets the research agenda for the future. By “digital writing,” we colloquially mean the use of electronic computing hard- ware and software to write, typically involving personal computers in the form of desktop machines or laptops with programs designed for composing and editing text. More narrowly, digital writing uses an electronic medium to record, store, and display text. Letters and words are inputted through an interface that translates analogue continuous signals into discrete digital ones, removing noise and allowing for retrieval, reproduction, and modification. In a broader semiotic sense, all writing can be called digital because every true writing system makes use of a finite set of discrete and arbitrary elements, the characters or graphemes of the script (see also Goodman, 1968). This book deals only with digital writing in the narrower sense.
Digital Writing Technologies in Higher Education: Theory, Research, and Practice
Keywords: Digital Engagement; Technology in Education; Writing technologies; Writing/Composition Education